2013
DOI: 10.1021/ol400277h
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael Addition of N-tert-Butanesulfinyl Imidate with α,β-Unsaturated Diesters: Scope and Application to the Synthesis of Indanone Derivatives

Abstract: An additive-free and highly diastereoselective Michael addition reaction of an N-tert-butanesulfinyl imidate to α,β-unsaturated diesters has been developed using LDA as a base with good to excellent yields. The utility of this chemistry is further demonstrated by the asymmetric synthesis of 3-substituted indanone derivatives 8a, 8d, 8e, and 8i with high enantiomeric excess, which are potential building blocks for preparing biologically active lead compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…It should be noted that vinyl triflates are in great demand for organic synthesis of cross-couplings and other reactions. , Concerning indanones, much effort is given to their synthesis due to the biological activity of these compounds. , …”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that vinyl triflates are in great demand for organic synthesis of cross-couplings and other reactions. , Concerning indanones, much effort is given to their synthesis due to the biological activity of these compounds. , …”
Section: Resultsmentioning
confidence: 99%
“…The retrosynthetic analysis of (À)-isoschizogamine (1)a nd (À)-2-hydroxyschizogamine (15)i ss hown in Scheme1.W e envisioned that the amide bond in isoschizogamine (1) Based on the retrosynthetic analysis, we began the total synthesis by preparing the intermediate 20 with C, D, and Er ings (Scheme 2). Our group and Liu'sg roup [13,14] have reported that chiral N-tert-butanesulfinyl imidate-induced [15] Michael addition to a,b-unsaturatede ster usually provides adducts with excellent yields and diastereoselectivities. The addition reaction of imidate (R)-24 with diester 25 afforded two separabled iastereomers 26 a and 26 b in a5 :1 ratio in 90 %c ombined yield.…”
Section: Resultsmentioning
confidence: 99%
“…Both diastereomers 5 and 6 could be separated after column chromatography and subjected to chemical transformations separately. Decarboxylation of either 5 or 6 upon treatment with tetraethylammonium hydroxide20 in DMSO gave the monoesters 7 and 8 in 70 and 60 % yield, respectively. Finally, we carried out the lactamization of compounds 5 and 7 to give the chiral piperidones 9 21 and 10 , respectively, by basic treatment with lithium hexamethyl disilazide (LiHMDS) in toluene 22…”
Section: Resultsmentioning
confidence: 99%